A137 AN ELUSIVE GASTROINTESTINAL BLEED: A CASE OF RUPTURED CYSTIC ARTERY PSEUDOANEURYSM WITH PREVIOUS BILLROTH-II SURGERY. (21st February 2022) - Jiang, S X; Murray, T; Leung, V T; Ou, G
Abstract: Background: Cystic artery pseudoaneurysm (CAP) is a rare but potentially life-threatening cause of upper gastrointestinal (GI) bleeding and requires urgent intervention. Aims: To describe the clinical enigma of CAP in the context of distorted anatomy and discuss management. Methods: Case report and review of literature Results: Case Report A healthy 91-year-old man with a remote history of gastric ulcer perforation leading to Billroth-II surgery 40 years ago presented to a community hospital with melena. He had no abdominal pain and liver enzymes were normal. His hemoglobin was 97 g/L (from 137 g/L the month prior) with a BUN:Cr ratio of 50.6 mg/dL and white cell count of 14.4 x10 9 /L. Upper endoscopy identified a large adherent clot in the stomach that could not be dislodged and was suspected to obscure the culprit lesion. Afferent and efferent limbs from previous Billroth-II surgery were identified but not intubated. He was managed supportively with acid suppression and blood transfusion, but his hemoglobin continued decreasing, leading to transfer to a tertiary centre. Upon arrival he had new-onset abdominal pain, rigors, and diaphoresis with a heart rate of 175 beats/minute and blood pressure of 75/40 mmHg. After resuscitation, emergent CT angiogram demonstrated acute contrast extravasation into the gallbladder in keeping with a ruptured CAP. He underwent successful coiling of the cystic artery. Following this, his abdominal pain resolved, and hemoglobin stabilized. Repeat endoscopy demonstrated Billroth-II anatomy without bleeding lesion. He was treated with antibiotics for presumed cholecystitis and discharged home for outpatient cholecystectomy. Literature Review CAP is a rare cause of hemobilia, described only in case reports. The complete hemobilia triad of jaundice, right upper quadrant pain, and GI bleeding is absent in the majority of cases, requiring endoscopic evaluation of the ampulla of Vater or contrast CT. The most common causes of CAP are iatrogenic from cholecystectomy, cholecystitis, gallstones, and malignancy. These mechanisms, whether through trauma or inflammation, lead to damage of the gallbladder wall and the cystic artery. Contained CAP can lead to intermittent bleeding whereas ruptured CAP causes brisk arterial bleeding, necessitating arterial embolization or emergent cholecystectomy. In cases of biliary obstruction, either from the original process or subsequent blood clot at the ampulla, ERCP can lead to successful decompression. Conclusions: We present a case of ruptured CAP which eluded diagnosis due to diagnostic rarity, lack of clinical clues, and distorted anatomy. CAP should be considered with a history of recent cholecystectomy, acute cholecystitis, or gallstones. Maintaining an index of suspicion for rare causes of GI bleeding can ensure timely diagnosis and escalation to the appropriate level of care. Funding Agencies: None